Heparin-induced thrombocytopaenia diagnostic testing after adult cardiac surgery: a single-centre experience and development. (5th November 2018) - Schaefer, Anne-Kristin; Donhauser, Beatrice; Kroeckel, Ivonne; Füreder, Lisa; Holaubek, Caroline; Braunschmid, Tamara; Mouhieddine, Mohamed; Panzer, Simon; Dworschak, Martin; Steinlechner, Barbara
Abstract: OBJECTIVES: To assess the incidence and outcome of heparin-induced thrombocytopaenia (HIT) in patients after cardiac surgery on cardiopulmonary bypass (CPB) and to review the time course of platelet counts and the use of different immunological diagnostic tests. METHODS: All patients ≥18 years of age who underwent CPB from 2006 to 2015 and who were postoperatively admitted to our cardiac intensive care unit (ICU) were included in this retrospective study. Screening for heparin/platelet factor-4 antibodies was performed using an antibody test, which was later replaced with a screening test specific for IgG antibodies without IgA/IgM cross-reactivity. The enzyme immunoassay (EIA) for the detection of antibodies of all immunoglobulin classes against heparin/PF4 complexes was replaced with an IgG-specific EIA. HIT was confirmed by a heparin-induced platelet aggregation test until 2014. RESULTS: Among 4978 patients admitted between 2006 and 2015, 539 (11%) patients were evaluated for HIT. Patients were excluded because of age <18 years ( n = 9), non-cardiac surgery without CPB ( n = 10) or incomplete data ( n = 3). Of the remaining 517 patients, 43 (8.3%) patients were HIT-positive. HIT incidence was 0.86%. The proportion of HIT-positive patients was similar in men and women (8.4% and 8.2%, respectively). Men and women with suspected HIT also had similar in-hospital mortality (odds ratio ≈ 1; P = 0.926). CONCLUSIONS: The incidence of HIT was lower in our study than previously reported. Novel immunological tests have improved to specifically detect IgG antibodies. Furthermore, they are able to detect anti-protamine antibodies, which may be present in patients with high clinical probability of testing negative for HIT. Incidence and clinical relevance of heparin/protamine antibodies will be subjects of future investigation.